Past testate amoeba communities in landslide mountain fens (Polish Carpathians): The relationship between shell types and sediment. (June 2021) - Marcisz, Katarzyna; Buczek, Krzysztof; Gałka, Mariusz; Margielewski, Włodzimierz; Mulot, Matthieu; Kołaczek, Piotr
Landslide mountain fens formed in landslide depressions are dynamic environments as their development is disturbed by a number of factors, for example, landslides, slopewash, and surface run-off. These processes lead to the accumulation of mineral material and wood in peat. Disturbed peatlands are interesting archives of past environmental changes, but they may be challenging for providing biotic proxy-based quantitative reconstructions. Here we investigate long-term changes in testate amoeba communities from two landslide mountain fens – so far an overlooked habitat for testate amoeba investigations. Our results show that abundances of testate amoebae are extremely low in this type of peatlands, therefore not suitable for providing quantitative depth-to-water table reconstructions. However, frequent shifts of dominant testate amoeba species reflect dynamic lithological situation of the studied fens. We observed that high and stable mineral matter input into the peatlands was associated with high abundances of species producing agglutinated (xenosomic) as well as idiosomic shells which prevailed in the testate amoeba communities in both analyzed profiles. This is the first study that explores testate amoebae of landslide mountain fens in such detail, providing novel information about microbial communities of these ecosystems.